2015
DOI: 10.1152/ajplung.00294.2014
|View full text |Cite
|
Sign up to set email alerts
|

ADAM-family metalloproteinases in lung inflammation: potential therapeutic targets

Abstract: -Acute and chronic lung inflammation is driven and controlled by several endogenous mediators that undergo proteolytic conversion from surface-expressed proteins to soluble variants by a disintegrin and metalloproteinase (ADAM)-family members. TNF and epidermal growth factor receptor ligands are just some of the many substrates by which these proteases regulate inflammatory or regenerative processes in the lung. ADAM10 and ADAM17 are the most prominent members of this protease family. They are constitutively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 223 publications
(236 reference statements)
0
107
0
1
Order By: Relevance
“…The HCRs in CD99 are characterized by many aspartate residues, which are greatly preferred by meprin b (6), indicating possible coevolution of protease and substrate. As a consequence of these negatively charged motifs, CD99 is not cleaved by ADAM10/17, metalloproteases that prefer aliphatic amino acids (42) and have been shown to shed other adhesion molecules involved in TEM [e.g., JAM-A or L-selectin (1,43,44)]. This finding further demonstrates the specificity of meprin b for CD99.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The HCRs in CD99 are characterized by many aspartate residues, which are greatly preferred by meprin b (6), indicating possible coevolution of protease and substrate. As a consequence of these negatively charged motifs, CD99 is not cleaved by ADAM10/17, metalloproteases that prefer aliphatic amino acids (42) and have been shown to shed other adhesion molecules involved in TEM [e.g., JAM-A or L-selectin (1,43,44)]. This finding further demonstrates the specificity of meprin b for CD99.…”
Section: Discussionmentioning
confidence: 69%
“…Regulated intramembrane proteolysis (RIP) of cell adhesion molecules, such as junctional adhesion molecule (JAM)-A, intercellular adhesion molecule (ICAM)-1, and L-selectin, was shown to be essential for transendothelial migration (TEM) of inflammatory or cancer cells (1). Meprin b, a multidomain type I transmembrane metalloprotease, is an initiator of RIP, and structural studies revealed dimeric formation of the protease with the active site in proximity to the cell surface (2)(3)(4).…”
mentioning
confidence: 99%
“…27 Following birth, experiments with conditional knockout mice suggest a critical role for ADAM17 in regulating immunity, inflammation and bone formation. [30][31][32] In contrast to the situation in mice, ADAM17 may not be required for development in humans. Recently, 2 families with a genetic deficiency of ADAM17 were identified.…”
mentioning
confidence: 96%
“…Hla treatment of airway epithelial cells results in activation of ADAM10 (60), which may affect several subsequent signaling modules by as yet unknown links in the transduction pathways including proinflammatory pathways (13). However, ADAM10 activation depends on the presence of extracellular calcium (25) and on calcium influx into the cytosol (23 (4,19,43), but the modes of activation are still elusive.…”
mentioning
confidence: 99%